Musical perceptual skills, but not neural auditory processing, are associated with better reading ability in childhood - Partanen Eino; Kivimäki Riia; Huotilainen Minna; Ylinen Sari; Tervaniemi Mari (Elsevier, 2022)
Musical activities have been suggested to be beneficial for language development in childhood. Randomised controlled trials using music have indicated that musical interventions can be used to support language skills in children with developmental language difficulties. However, it is not entirely clear how beneficial music activities are for normally developing children or how the effects mediated via music are transmitted. To investigate these questions, the present study used structural equation models to assess how musical training, perceptual musical skills, and auditory processing in the brain are associated with reading proficiency and each other. Perceptual musical skills were assessed using musicality tests while auditory processing in the brain was measured using mismatch negativity responses to pitch, duration, and phoneme length contrasts. Our participants were a community sample of 64 8–11-year-old typically developing children with and without musical training, recruited from four classes in four elementary schools in Finland. Approximately half of children had music as a hobby. Our results suggest that performance in tests of musical perceptual skills is directly linked with reading proficiency instead of being mediated via auditory processing in the brain. Auditory processing in the brain in itself seems not to be strongly linked with reading proficiency in these children. Our results support the view that musical perceptual skills are associated with reading skills regardless of musical training.